2019
DOI: 10.1149/2.0661906jes
|View full text |Cite
|
Sign up to set email alerts
|

Overcharge Behavior and Early Warning Analysis of LiNi0.5Co0.2Mn0.3O2/C Lithium-Ion Battery with High Capacity

Abstract: High-power lithium ion batteries have become the development focus of electric vehicles and large-scale energy storage devices. But it is also particularly critical to further study their hazardous properties under abuse conditions because higher capacity is more catastrophic. In this study, overcharge tests of 43 Ah cubic lithium ion batteries with different charge rates are conducted to study the thermal runaway behavior and parameter characteristics. Material characterization and thermal analysis tests furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…Until now, a quantity of research has been conducted to study the mechanism of overcharge. [17][18][19][20] Simultaneously, the influence of overcharge on the electrochemical [21][22][23] and thermal properties 24,25 is researched. When a battery experiences an overcharge condition, the cathode will be over-delithiated and the anode will be overlithiated, and a series of side reactions will accompany this condition.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, a quantity of research has been conducted to study the mechanism of overcharge. [17][18][19][20] Simultaneously, the influence of overcharge on the electrochemical [21][22][23] and thermal properties 24,25 is researched. When a battery experiences an overcharge condition, the cathode will be over-delithiated and the anode will be overlithiated, and a series of side reactions will accompany this condition.…”
Section: Introductionmentioning
confidence: 99%
“…The current research on overcharge‐induced thermal runaway is mainly focused on new batteries . Leising et al conducted overcharge abuse test on lithium‐ion battery with LiCoO 2 cathode.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the pouch battery had better overcharge tolerance in the early stage of overcharge, while the prismatic battery had better thermal runaway buffering performance in the late stage. Jiang et al studied the voltage characteristics of lithium‐ion battery overcharged under various current rates, and proposed an early warning analysis method for thermal runaway. In addition, Ouyang's and Zhu' groups established the electrochemical‐thermal coupled model of lithium‐ion battery under overcharge, which deepened the understanding of thermal runaway mechanism of the new Li‐ion battery.…”
Section: Introductionmentioning
confidence: 99%
“…Although commercial batteries occupy a wider range of applications, they are accompanied by unknown composition and complicated structure. To solve that, coin cell can be used to further analyze the structure changes of materials and explain the phenomenon that occurs in the power battery [19]. The simple composition and structure of coin cell can reflect the performance of the material itself.…”
Section: Introductionmentioning
confidence: 99%